Financial Statement Fraud: A Look at the Top Three - Wijaya, Shirley; Indriyani, Kristi (Account: Jurnal Akuntansi, Keuangan dan Perbankan, 2025)
The objective of this study is to determine the impact of the fraud triangle which includes pressure, opportunity, and rationalization on the top three largest market capitalization based on the IDX Yearly Statistic 2024 report from 2021 to 2023. The data is taken from IDX annual report. The study is quantitative in nature and adopts a descriptive approach. The result shows that total asset turnover ratio (X1b), representing pressure, has positive and significant influence on financial statement fraud. Meanwhile, managerial ownership (X1c) and inventory turnover ratio (X2b) have a negative effect on financial statement fraud. Finally, return-on-asset (X1a), leverage ratio (X1d), independent commissioners (X2a), and change in auditor (X3) have no effect on financial statement fraud. This study will raise awareness to various companies’ stakeholders to create adequate regulation to prevent fraud. It will also be impactful for further research as it can be used as a reference for research. Keyword: Fraud Triangle, Annual Report, Financial Statement, Stakeholder, Quantitative